Modulation of stromal cell-derived factor 1 alpha (SDF-1α) and its receptor CXCR4 in Porphyromonas gingivalis-induced periodontal inflammation. Issue 1 (December 2017) - Sun, Jiang; Nemoto, Eiji; Hong, Guang; Sasaki, Keiichi
Abstract Background The production of chemokines by tissue resident cells during inflammation is considered one of the main mechanisms involved in the formation of inflammatory infiltrates. Fibroblasts are the main resident cell type in gingival and periodontal ligament tissues, and their ability to produce chemokine stromal cell-derived factor 1 alpha (SDF-1α) and its receptor CXCR4 under stimulation by gram negative bacteria, Porphyromonas gingivalis, commonly found in periodontal infections was investigated. Methods Western blots were used to assess SDF-1α and CXCR4 protein expression levels in human gingival fibroblast cells (HGF-1) induced by Lipopolysaccharide (LPS) fromP. gingivalis in the presence or absence of LY294002, a highly selective inhibitor of PI-3K/Akt. RT-PCR and quantitative Real-time PCR was performed using gingival mRNAs from periodontitis patients. Immunohistochemistry was performed to analyze the expression and subcellular localization of SDF-1α and CXCR4, together with NF-kβ phosphorylation, in specimens from patients with periodontitis and in an experimental rat periodontitis model. Results We found thatP. gingivalis LPS up-regulated SDF-1α and CXCR4 protein levels and elevated phosphorylation of the SDF-1α-responsive NF-kβ and Akt at 24 h in HGF-1 cells. SDF-1α and CXCR4 mRNA and protein expression levels were high in all patients with periodontitis. In theP. gingivalis -induced rat experimental periodontitis model, SDF-1α and CXCR4 immunoreactivity was higher in gingival and periodontal ligament tissues compared to the control. Conclusion Our data showed that PI-3K/Akt is an upstream participant in theP. gingivalis LPS-mediated induction of SDF-1α. Taken together, these results suggest that the chemokine SDF-1α and its receptor CXCR4 contribute toP. gingivalis -induced periodontal inflammation.